Severity of maxillofacial injuries and associated factors in brazilian women victims of domestic violence (Research, Society and Development, 2020)
Objective: The aim of this study was to determine the profile and prevalence of maxillofacial injury (MFI) and to assess associated factors in women victims of domestic violence. Methodology: This was a cross-sectional and analytical study that evaluated 514 records of women victims of domestic violence diagnosed with MFI attended at a public reference urgency and trauma hospital in Northeastern Brazil. Descriptive and multivariate statistics were performed using Poisson regression. Results: The prevalence of fractures and facial lacerations was 80.2% and 19.8%, respectively, the majority with low severity (92.1%). Associations were observed between MFI severity and alcohol / drug consumption by the perpetrator (PR=0.251; 95%CI=0.106-0.595; p=0.002) and the night shift (PR=4.675; 95%CI= 1.745-12.525; p=0.002). Correlations were found between MFI severity and length of hospital stay (r=0.148; p